MiR‐378a regulates keratinocyte responsiveness to interleukin‐17A in psoriasis. (1st August 2022) - Xia, Ping; Pasquali, Lorenzo; Gao, Chenying; Srivastava, Ankit; Khera, Nupur; Freisenhausen, Jan Cedric; Luo, Longlong; Rosén, Einar; van Lierop, Anke; Homey, Bernhard; Pivarcsi, Andor; Sonkoly, Enikö
Abstract: Background: Psoriasis is an immune‐mediated inflammatory skin disease, in which an interplay between infiltrating immune cells and keratinocytes sustains chronic skin inflammation. Interleukin (IL)‐17A is a key inflammatory cytokine in psoriasis and its main cellular targets are keratinocytes. Objectives: To explore the role of miR‐378a in psoriasis. Methods: Keratinocytes obtained from psoriatic skin and healthy epidermis were separated by magnetic sorting, and the expression of miR‐378a was analysed by quantitative polymerase chain reaction. The regulation and function of miR‐378a was studied using primary human keratinocytes. The expression of miR‐378a was modulated by synthetic mimics, and nuclear factor kappa B (NF‐κB) activity and transcriptomic changes were studied. Synthetic miR‐378a was delivered to mouse skin in conjunction with induction of psoriasiform skin inflammation by imiquimod. Results: We show that miR‐378a is induced by IL‐17A in keratinocytes through NF‐κB, C/EBP‐β and IκBζ and that it is overexpressed in psoriatic epidermis. In cultured keratinocytes, ectopic expression of miR‐378a resulted in the nuclear translocation of p65 and enhanced NF‐κB‐driven promoter activity even in the absence of inflammatory stimuli. Moreover, miR‐378a potentiated the effect of IL‐17A on NF‐κB nuclear translocation and downstream activation of the NF‐κB pathway. Finally, injection of miR‐378a into mouse skin augmented psoriasis‐like skin inflammation with increased epidermal proliferation and induction of inflammatory mediators. Mechanistically, miR‐378a acts as a suppressor of NFKBIA/IκBζ, an important negative regulator of the NF‐κB pathway in keratinocytes. Conclusions: Collectively, our findings identify miR‐378a as an amplifier of IL‐17A‐induced NF‐κB signalling in keratinocytes and suggest that increased miR‐378a levels contribute to the amplification of IL‐17A‐driven skin inflammation in psoriasis.